2015
DOI: 10.3390/agriculture5030742
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxicosis: Lessons from Toxicity and Responses to Aflatoxin B1 in Poultry

Abstract: This review is a comprehensive introduction to the effects of poultry exposure to the toxic and carcinogenic mycotoxin aflatoxin B1 (AFB1). The relationship between AFB1 sensitivity and metabolism, major direct and indirect effects of AFB1, recent studies of gene expression and transcriptome responses to exposure, and mitigation strategies to reduce toxicity are discussed. Exposure to AFB1 primarily occurs by consumption of contaminated corn, grain or other feed components. Low levels of residual AFB1 in poult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 281 publications
(478 reference statements)
4
112
0
3
Order By: Relevance
“…Turkeys, ducks, and quail are considered more sensitive to aflatoxins than chicken, but the effects in the animals are basically the same (Monson, Coulombe, and Reed 2015). The effects of aflatoxins on poultry production have been reviewed (Feddern et al 2013;Monson, Coulombe, and Reed 2015), showing an association with reduced egg production, reduced egg weight, and increased poultry mortality due to renal, hepatic, gastrointestinal, and immunological impacts.…”
Section: Impact On Livestock Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Turkeys, ducks, and quail are considered more sensitive to aflatoxins than chicken, but the effects in the animals are basically the same (Monson, Coulombe, and Reed 2015). The effects of aflatoxins on poultry production have been reviewed (Feddern et al 2013;Monson, Coulombe, and Reed 2015), showing an association with reduced egg production, reduced egg weight, and increased poultry mortality due to renal, hepatic, gastrointestinal, and immunological impacts.…”
Section: Impact On Livestock Productivitymentioning
confidence: 99%
“…The effects of aflatoxins on poultry production have been reviewed (Feddern et al 2013;Monson, Coulombe, and Reed 2015), showing an association with reduced egg production, reduced egg weight, and increased poultry mortality due to renal, hepatic, gastrointestinal, and immunological impacts. However, the data on how aflatoxin affects weight gain in poultry are not consistent, and some experiments with aflatoxins up to 2.5 ppm have failed to show effects (Dersjant-Li, Verstegen, and Gerrits 2003).…”
Section: Impact On Livestock Productivitymentioning
confidence: 99%
“…Resistance to aflatoxin in chickens is higher than in other animals and susceptibility varies with breed, species, age, dose and length of exposure (Monson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins are the most intensively researched group of mycotoxins, and the effects of aflatoxins on broiler productivity have been previously reviewed (Kensler et al, 2011;Yunus et al, 2011;Monson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin and Aflatoxicosis due to the consumption of contaminated diets in poultry are accompanied with symptoms such as decreased performance, liver damages and immunosuppression [2] . The investigations revealed that Cytochrome P450 enzyme 1 produced by CYP1A5 and CYP3A37 genes is specifically responsible for the conversion of aflatoxin to the other metabolites at in in vitro and in vivo conditions [3,4] . CYP450 1A5 enzyme has high affinity for binding and metabolizing the metabolites of aflatoxin as well as the detoxification of AFM 1 [5] .…”
Section: Introductionmentioning
confidence: 99%